Peningkatan kadar kortisol serum pada mahasiswi obesitas setelah latihan akut intensitas sedang - Puspitorini, Wahyuningtyas; Soemardiawan, Soemardiawan; Annamayra, Ajeng; Suharto, Taufik Hidayat; Pranoto, Adi (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2023)
Obesity is a condition that can cause metabolic stress by activating the HPA axis, which impacts increasing stress levels characterized by increased cortisol secretion. The present research aims to investigate the impact of moderate-intensity acute exercise on decreasing cortisol levels among obese female students. A true-experimental method with a pretest-posttest control group design was utilized to conduct the study. A total of 20 female students between the ages of 20 and 23, with a BMI ranging from 25-28 kg/m2, voluntarily participated in the research. The participants were divided into two groups: control (n=10) and exercise (n=10) - the latter group being exposed to moderate-intensity acute exercise once as an intervention, with 40-minute sessions and an intensity level of 60-70% HRmax using the Treadmill Life Fitness equipment. The serum cortisol levels were measured through the ELISA 30 minutes pre-exercise and 6 hours post-exercise. The collected data were analyzed using an independent sample t-test with a 5% significance level. The study's findings will help compare the mean serum cortisol levels between the control and exercise groups. Based on the results of the study, it was found it can be concluded that moderate-intensity acute exercise carried out for 40 minutes/exercise session was effective in reducing serum cortisol levels in obese female students. We recommend exercise to overcome stress-related metabolic health problems in individuals with obesity.